Forest Resource Information on the Internet: Connecting to Today's On-line Resources - Chris Demers (EDIS)
FOR-124, a 4-page fact sheet by Chris Demers, replaces a 1997 document with updated information on Internet technology and the latest forest resource Web sites available. Published by the UF School of Forest Resources and Conservation, August 2007.